2012
DOI: 10.5171/2012.349927
|View full text |Cite
|
Sign up to set email alerts
|

Management Accounting Change: ABC Adoption and Implementation

Abstract: The current research tries to contribute to the successful design and implementation of ABC in the context of Jordanian Manufacturing Companies. In order to satisfy the research objectives, both quantitative and qualitative data are gathered. For the quantitative data, a questionnaire survey was developed for the determination of the present scenario involving ABC adoption and implementation. For the qualitative one, semi-structured interviews were utilized to find out the factors impacting the adoption and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In the Jordanian context, Nassar et al (2011) found that about 25% of the respondents were using ABC, whereas about 10% were using ABM. Similarly, Fadzil and Rababah (2012) also found that about 20% of Jordanian manufacturing companies were using ABC. A survey among large Norwegian manufacturing companies (Berg et al, 2018) showed that only 20% used ABC to a large extent and 40% did not use ABC at all.…”
Section: Adoption and Diffusionmentioning
confidence: 87%
“…In the Jordanian context, Nassar et al (2011) found that about 25% of the respondents were using ABC, whereas about 10% were using ABM. Similarly, Fadzil and Rababah (2012) also found that about 20% of Jordanian manufacturing companies were using ABC. A survey among large Norwegian manufacturing companies (Berg et al, 2018) showed that only 20% used ABC to a large extent and 40% did not use ABC at all.…”
Section: Adoption and Diffusionmentioning
confidence: 87%
“…Fei and Isa (2010) noted that the majority of research on ABC/M implementation uses a quantitative research approach. Consistent with this view, this investigation uses a survey questionnaire to extract data on the adoption of ABC and ABM, a methodology often used in studies of a similar focus (Al-Omiri and Drury, 2007; Askarany and Yazdifar, 2012; Bhimani et al ., 2007; Bjornenak, 1997; Innes et al ., 2000; Fadzil and Rababah, 2012; Schoute, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…They noted that Chinese companies were not as advanced in terms of office and accounting computerisation as those in the West. Fadzil and Rababah (2012) studied the contribution of effective design and application of ABC within the framework of Jordanian manufacturing companies. They found that 19.5 per cent of Jordanian manufacturing companies had a high level of satisfaction with ABC.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies (e.g. Arnaboldi & Lapsley, 2003;Byrne, Stower & Torry, 2009;Chung, Schoch & Teoh, 1997;Faudziah & Rababah, 2011, 2012Rasiah, 2011;Velmurugan & Nahar, 2010). They also evidenced that those companies who adopted ABC are still in the infancy phase of implementation as most companies who tried implementing it ultimately succeeded in employing its narrow application in trivial services and in unused systems.…”
Section: Introductionmentioning
confidence: 94%